Synthesis and chiroptical characterization of a negatively curved helicene with a central tropone unit - Kies, Wolfgang; Misselwitz, Erik; Borstelmann, Jan; Berger, Georg; Rominger, Frank; Kivala, Milan (Synlett, 2025)
We report the synthesis of an π-expanded [5]helicene incorporating a seven-membered tropone unit. The synthesis was based on a cycloaddition-cyclization strategy that exploited the versatile reactivity of alkynes. X-ray crystallographic analysis of the racemic compound revealed its highly twisted structure and provided insights into the structural impacts of the tropone moiety on the [5]helicene subunit. Enantiomeric resolution by chiral HPLC followed by an assessment of the configurational stability revealed a significantly reduced barrier for racemization compared to pristine [5]helicene. Density functional theory calculations on the racemization mechanism identified the crucial role of the flexible tropone unit in preorganizing the molecular framework toward the transition-state geometry, thereby lowering the activation barrier.
Gesehen am 23.02.2026